2022
DOI: 10.1021/acsami.2c00231
|View full text |Cite
|
Sign up to set email alerts
|

Defect Passivation through (α-Methylguanido)acetic Acid in Perovskite Solar Cell for High Operational Stability

Abstract: Defect passivation has become essential in improving efficiency and stability in perovskite solar cells. Here, we report the use of (α-methylguanido)acetic acid, also known as creatine, as a passivation molecule. It is employed both as an additive and as a surface passivation layer of perovskite thin films, given its multiple functional groups, which could address different defect sites, and its size, which could inherently affect the material structure. We prove that the surface passivation is more efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In contrast to the control perovskite, the NH 3 +, and C=O stretching peaks were slightly shifted, likely a result of interactions between the oxygen in the carboxyl group and tin. [24,25] This observation implies that l-Asn zwitterion in tin perovskites can introduce nucleation sites, retard the crystallization rate and induce vertical crystal orientation, leading to the improved crystal quality of perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the control perovskite, the NH 3 +, and C=O stretching peaks were slightly shifted, likely a result of interactions between the oxygen in the carboxyl group and tin. [24,25] This observation implies that l-Asn zwitterion in tin perovskites can introduce nucleation sites, retard the crystallization rate and induce vertical crystal orientation, leading to the improved crystal quality of perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…Ji et al reported difunctionalized BTZI-TPA-passivated perovskite with a champion PCE of 24.06%, where the molecule formed a stronger interaction with uncoordinated Pb 2+ on the perovskite surface; consequently, the non-radiative recombination of the perovskite was significantly reduced . −COO–, −C­(NH)­NH 2 functional group-containing (α-methylguanido)­acetic acid-passivated (FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 produced a maximum PCE of 22.6% . Post-treatment of Cs 0.03 (FA 0.90 MA 0.10 ) 0.97 PbI 3 by 2D oleylammonium iodide-based passivation demonstrated more than 24% PCE .…”
Section: Introductionmentioning
confidence: 99%
“…34 −COO−, −C(�NH)NH 2 functional group-containing (αm e t h y l g u a n i d o ) a c e t i c a c i d -p a s s i v a t e d ( F A P -bI 3 ) 0.95 (MAPbBr 3 ) 0.05 produced a maximum PCE of 22.6%. 35 Post-treatment of Cs 0.03 (FA 0.90 MA 0.10 ) 0.97 PbI 3 by 2D oleylammonium iodide-based passivation demonstrated more than 24% PCE. 36 Additionally, 3-(trifluoromethyl)phenethylamine hydroiodide (CF 3 PEAI) was employed for post-surface passivation, where it coordinated with the uncoordinated Pb 2+ and modified defects.…”
mentioning
confidence: 97%
“…1−6 However, their instability toward water, humidity, high temperature, and strong light irradiation, and, in addition, the toxicity of certain elements, such as lead, limit their applications. Factually, their stability has been improved substantially by many methods including surface passivation with an organic or inorganic shell, 7,8 encapsulation by a polymer, 8−10 lattice site substitution, 11 etc. Recently, researchers have generated considerable interest in glass-ceramics in order to address the instability of MHs.…”
Section: Introductionmentioning
confidence: 99%